A new approach for teaching power electronics in electrical engineering courses - Riehl, Rudolf Ribeiro [UNESP]; Ulson, Jose Alfredo Covolan [UNESP]; Andreoli, Andre Luiz [UNESP]; Alves, Alceu Ferreira [UNESP] (Institute of Electrical and Electronics Engineers (IEEE), 2015)
This work presents a new approach for teaching activities at the Laboratory of Power Electronics, at the Undergraduate Electrical Engineering course of the Faculty of Engineering Bauru (UNESP). The proposal is to develop a practical project of a bridge rectifier with Power Factor correction. Students of the course are encouraged to develop at first, the theoretical study of the rectifier, including and not-including Power Factor correction. After this study, the project characteristics such as voltage, current and power in the load, supply voltage, switching frequency, efficiency and Power Factor are defined, at the same time the choice of dedicated integrated circuit to control and correct the Power Factor to be used is done. Components of the power stage as well as the control loop parts are defined based on design features. The next step is the generation of the circuit schematic and the PCB layout for manufacturing the printed circuit board. Once the circuit is all done, students are ready to follow a procedure set to study characteristics and performance parameters of the rectifier. Measurements are first performed on the load side and then on the mains side, with and without correction of Power Factor and after that, the performance parameters in both situations are calculated. Tables of performance parameters due the variation of the supply voltage are generated, with and without correction of the Power Factor and the same curves are plotted for comparison, analysis, and discussion for the proposed project.
Keywords: Education in Electrical Engineering; Power Electronics Teaching; Power Factor Correction